Nivolumab-Induced de novo Discoid Lupus Erythematosus - Jaya Manjunath; Mark Mochel; Fnu Nutan (Case Reports in Dermatology, 2022)
An increasing number of checkpoint inhibitor-induced subacute cutaneous lupus erythematosus events have been reported. We present the first case of nivolumab-induced discoid lupus erythematosus in a patient with hepatocellular carcinoma. The patient presents with violaceous hypopigmented plaques on the pinna bilaterally, hypopigmented plaques with central hyperpigmentation on the posterior neck, and other hypopigmented plaques on the face, forearms, and hands. For management, nivolumab was held for 2 months, and Plaquenil and topical steroids were added. Nivolumab was resumed with no further progression of DLE lesions and improvement of the skin. It is important to characterize cutaneous side effects to effectively manage them.